Best interests and potential organ donors. Issue 7657 (12th June 2008) - Coggon, John; Brazier, Margaret; Murphy, Paul; Price, David; Quigley, Muireann
Abstract : Many potential donor organs are currently lost because of misunderstanding of the law. John Coggon and colleagues clarify what is permissible in non-heart-beating donation